2009
DOI: 10.1002/prca.200900071
|View full text |Cite
|
Sign up to set email alerts
|

The use of phosphate‐affinity SDS‐PAGE to measure the cardiac troponin I phosphorylation site distribution in human heart muscle

Abstract: We have used phosphate affinity SDS-PAGE to separate the phosphorylated species of cardiac troponin I (cTnI). To test the method we phosphorylated pure cTnI with protein kinase A catalytic subunit and observed up to six bands corresponding to 0, 1P, 2P, 3P, 4P and 5P phospho-species. We examined the phospho-species of cTnI in human heart myofibrillar extracts by phosphate affinity SDS-PAGE and Western blotting with a non-specific troponin I (TnI) antibody. In donor heart samples the bis-phosphorylated species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
87
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 45 publications
8
87
2
Order By: Relevance
“…These septal samples are characterized by a low level of phosphorylation of MyBP-C and troponin I (29,30,(55)(56)(57). In contrast, the two samples examined here, from free wall and from the atrial-septal junction region, showed high levels of phosphorylation similar to those in donor hearts (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 68%
“…These septal samples are characterized by a low level of phosphorylation of MyBP-C and troponin I (29,30,(55)(56)(57). In contrast, the two samples examined here, from free wall and from the atrial-septal junction region, showed high levels of phosphorylation similar to those in donor hearts (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 68%
“…phosphorylated, cTnI-DA mimics Ser 23 phosphorylated and Ser 24 unphosphorylated, and cTnI-AA mimics both sites unphosphorylated. Force development was measured at various Ca 2ϩ concentrations in permeabilized cardiomyocytes in which the endogenous troponin complex was exchanged with these recombinant human troponin complexes.…”
mentioning
confidence: 99%
“…This positive lusitropic effect may be induced by a decrease in myofilament Ca 2ϩ sensitivity (32,35,51) and by enhanced cross-bridge cycling kinetics (11,20,33). It is well established (mainly from studies in rodents) that phosphorylation of cTnI at the PKA sites Ser 23 and Ser 24 leads to a decrease in myofilament Ca 2ϩ sensitivity, through a conformational change of the troponin complex. This structural change reduces the affinity of Ca 2ϩ binding to cTnC (16,30).…”
mentioning
confidence: 99%
See 2 more Smart Citations